Glass-patternable notch-shaped microwave architecture for on-chip spin detection in biological samples. Issue 13 (5th May 2022) - Oshimi, Keisuke; Nishimura, Yushi; Matsubara, Tsutomu; Tanaka, Masuaki; Shikoh, Eiji; Zhao, Li; Zou, Yajuan; Komatsu, Naoki; Ikado, Yuta; Takezawa, Yuka; Kage-Nakadai, Eriko; Izutsu, Yumi; et al.
Abstract : This on-chip device realizes large-area and predictable spin detection of fluorescent nanodiamonds, providing a scalable platform for quantum-sensor-based bioassay. Abstract : We report a notch-shaped coplanar microwave waveguide antenna on a glass plate designed for on-chip detection of optically detected magnetic resonance (ODMR) of fluorescent nanodiamonds (NDs). A lithographically patterned thin wire at the center of the notch area in the coplanar waveguide realizes a millimeter-scale ODMR detection area (1.5 × 2.0 mm 2 ) and gigahertz-broadband characteristics with low reflection (∼8%). The ODMR signal intensity in the detection area is quantitatively predictable by numerical simulation. Using this chip device, we demonstrate a uniform ODMR signal intensity over the detection area for cells, tissue, and worms. The present demonstration of a chip-based microwave architecture will enable scalable chip integration of ODMR-based quantum sensing technology into various bioassay platforms.